Utilization Of Ginger Rhizomes As Immune System Improvement During The Covid-19 Pandemic In Jati Village - Niknik Handayani; Anisa Sofiani Fima; Fajar J Nugraha; Indah Wulansari; Ira Sapartira Hidayati; Liza Rizky Ayunani; Yusri Aulia (Fakultas Kewirausahaan Universitas Garut, 2021)
Abstract : Coronavirus Disease 2019, known as COVID-19, is something new and shocks the world, especially in Indonesia. This corona virus must be wary, because it spreads very quickly. In addition, the efforts are needed to increase the body's immune system, considering that viruses can enter the human body when the immune system decreases. The body's immune system is important to maintain during the current covid-19 period. One of the natural resources with low prices and contain high antioxidant is ginger rhizome. The Ginger Rhizome really helps the people in increasing the immune system. This community service activity was carried out in Jati Village by making ginger ‘wedang’ powder which was named